UPAYA PENINGKATAN AKTIVITAS BELAJAR IPS DENGAN METODE DEMONSTRASI PADA SISWA KELAS V SEKOLAH DASAR NEGERI 1 GEDUNG AIR BANDAR LAMPUNG TP 2019/2020 - Saring, Yahno (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2020)
Based on the pre-research results of the implementation of social studies learning (1) learning activities are still dominated by teachers so that students are less active in learning (2) the method used in social studies learning is the lecture method, where the information/concepts being studied are notified or presented by the method. lecture only; (3) in the learning process the teacher does not provide reinforcement in the form of providing motivation to students. The problem formulation in this study is